Nilai Perusahaan Ditinjau Dari Pengaruh Profitabilitas, Pertumbuhan Aset, Dan Struktur Modal Yang Dimoderasi Kebijakan Dividen: (Studi Empiris Pada Perusahaan Consumer Non-Cyclicals Yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Nur Rohmansah; Rahmat Taufik (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2026)
This study aims to examine the effect of profitability, asset growth, and capital structure on firm value with dividend policy as a moderating variable in Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange during the 2019–2023 period. This research employed a quantitative approach with an associative research design. The population consisted of 30 companies, while the sample was selected using purposive sampling, resulting in 19 companies with a total of 95 observations. The data were analyzed using panel data regression and Moderated Regression Analysis (MRA) with EViews 12. Based on the model selection tests, the Fixed Effect Model was identified as the most appropriate model. The results indicate that profitability has a positive and significant effect on firm value, implying that higher profitability leads to higher firm value. Asset growth also has a positive and significant effect on firm value, indicating that increasing assets enhance investors’ confidence in the company's future prospects. In contrast, capital structure has a negative and significant effect on firm value, suggesting that higher debt utilization tends to reduce firm value. Furthermore, dividend policy is not able to moderate the relationship between profitability and firm value, nor the relationship between asset growth and firm value. However, dividend policy is able to moderate the relationship between capital structure and firm value. These findings imply that capital structure decisions, together with dividend policy, play an important role in enhancing firm value.